2022
DOI: 10.1172/jci157101
|View full text |Cite
|
Sign up to set email alerts
|

CBFA2T3-GLIS2 model of pediatric acute megakaryoblastic leukemia identifies FOLR1 as a CAR T cell target

Abstract: The CBFA2T3-GLIS2 (C/G) fusion is a product of a cryptic translocation primarily seen in infants and early childhood and is associated with dismal outcome. Here, we demonstrate that the expression of the C/G oncogenic fusion protein promotes the transformation of human cord blood hematopoietic stem and progenitor cells (CB HSPCs) in an endothelial cell coculture system that recapitulates the transcriptome, morphology, and immunophenotype of C/G acute myeloid leukemia (AML) and induces highly aggressive leukemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…[76][77][78][79] Other antigen targets of interest in paediatric AML include mesothelin, CLEC12A (CLL-1, CD371), FLT3, FOL1R, and e-selectin ligand. [80][81][82][83][84][85][86] Early-phase paediatric studies of antibody-based or cellular immunotherapies against these targets are planned.…”
Section: Small Molecule Inhibitorsmentioning
confidence: 99%
“…[76][77][78][79] Other antigen targets of interest in paediatric AML include mesothelin, CLEC12A (CLL-1, CD371), FLT3, FOL1R, and e-selectin ligand. [80][81][82][83][84][85][86] Early-phase paediatric studies of antibody-based or cellular immunotherapies against these targets are planned.…”
Section: Small Molecule Inhibitorsmentioning
confidence: 99%
“…cord blood stem cells generated leukemia phenotypically similar to de novo disease. 20 Recent advancements in next-generation sequencing (NGS) have improved our understanding of the genomic landscape of AML. Several recent publications have identified cryptic or previously undetected translocations using NGS approaches.…”
Section: Molecular Targetsmentioning
confidence: 99%
“…The KMT2A gene at 11q23 can rearrange to create novel fusion proteins with a number of partner genes. More recent data demonstrate that specific fusions in infant AML delivered in a context appropriate manner may indeed be sufficient for malignant transformation, where transduction of CBFA2T3::GLIS2 or NUP98::KDM5A fusion transcript into normal cord blood stem cells generated leukemia phenotypically similar to de novo disease 20 …”
Section: Introductionmentioning
confidence: 99%
“…Analyses of transcriptomes were also a basis for identifying novel targets of C/G acute myeloid leukemia [ 66 ]. Namely, CAR-T cells directed against folate receptor α, encoded by the FOLR1 gene and identified in transcriptomic studies as a potential new target, revealed high efficacy in vitro and in experiments with xenograft models [ 66 ]. Interestingly, other transcriptomic investigations led to the proposal of development of a cellular therapy alternative based on CAR-T cells [ 67 ].…”
Section: Transcriptomics In Identifying New Target Diseases For Car-t...mentioning
confidence: 99%